Tuning the donor–acceptor interactions in phase-segregated block molecules. Issue 1 (6th October 2021) - Lamers, Brigitte A. G.; van Son, Martin H. C.; de Graaf, Freek V.; van den Bersselaar, Bart W. L.; de Waal, Bas F. M.; Komatsu, Kazuki; Sato, Hiroshi; Aida, Takuzo; Berrocal, José Augusto; Palmans, Anja R. A.; Vantomme, Ghislaine; Meskers, Stefan C. J.; et al.
Abstract : A robust, soft material held together by charge transfer interactions is developed. The nanostructure dimensions and material properties can be tuned by molecular design or pressure. Abstract : The assembly of donor–acceptor molecules via charge transfer (CT) interactions gives rise to highly ordered nanomaterials with appealing electronic properties. Here, we present the synthesis and bulk co-assembly of pyrene (Pyr) and naphthalenediimide (NDI) functionalized oligodimethylsiloxanes (oDMS) of discrete length. We tune the donor–acceptor interactions by connecting the pyrene and NDI to the same oligomer, forming a heterotelechelic block molecule (NDI-oDMSPyr), and to two separate oligomers, giving Pyr and NDI homotelechelic block molecules (Pyr-oDMS and NDI-oDMS). Liquid crystalline materials are obtained for binary mixtures of Pyr-oDMS and NDI-oDMS, while crystallization of the CT dimers occurred for the heterotelechelic NDI-oDMS-Pyr block molecule. The synergy between crystallization and phase-segregation coupled with the discrete length of the oDMS units allows for perfect order and sharp interfaces between the insulating siloxane and CT layers composed of crystalline CT dimers. We were able to tune the lamellar domain spacing and donor–acceptor CT interactions by applying pressures up to 6 GPa on the material, making the system promising for soft-material nanotechnologies. These results demonstrate the importance of the molecular design to tune the CT interactions and stability of a CT material.